Goodpasture's syndrome: treatment with plasmapheresis, immunosuppression, and anticoagulation. Issue 9 (September 1983) - Levin, M; Rigden, S P; Pincott, J R; Lockwood, C M; Barratt, T M; Dillon, M J
Abstract : We report 3 children with Goodpasture's syndrome. In 2 children the diagnosis was delayed, treatment began late, and they did not recover renal function. In the third child early diagnosis and intensive treatment with plasmapheresis, immunosuppression, and anticoagulation resulted in an initial return of renal function after a prolonged period of anuria. In this child, however, although there was no evidence of disease activity, further deterioration of renal function subsequently occurred.